The oretical aspects of formation of the mechanism of regulation of land relations - Movchan, S.; Yakunicheva, A.; Lezhenkin, I.; Kolomiiets, S. (Land Management, Cadastre and Land Monitoring, 2021)
The author considers the essence of economic category of land relations and reveals the factors that determine the peculiarities of land relations in the agrarian sphere and their regulation. The article describes the model of mechanism of regulation of land relations, represented as a set of structural and functional elements (a system of legal, economic, organizational and environmental regulators and subsystems of regulatory, informational, methodological, technical, and financial support) that allow using special methods and tools to influence the subjects of land relations within the framework of implementation of state land policy in order to achieve the objectives of state management of land relations. The author notes a paradoxical situation: there are large-scale real burdens of land plots involved in the process of agricultural production, but no established servitudes due to the absence of delimitation of ownership of encumbered land plots, as well as the absence of practices for their establishment. The specificity of land servitudes in agriculture is revealed. It consists of the following elements: 1) a significant share of land servitudes appeared in the pre-reform period when state ownership of land without registration of encumbrances was dominant; 2) low level of activity of the state in initiating the processes of formation of mechanisms for official recognition of land burdens, establishment of land servitudes and implementation of mandatory servitude payments; 3) the absence of uniform methods for determining the adequate compensation for burdening of productive lands; 4) the absence of mechanisms for reinvesting funds received by land owners in the form of servitude payments in the reproduction of land resources; 5) the absence of mechanisms for receiving servitude payments for encumbering the land plots, the ownership of which is not delimited.Key words: land relations, land resources, productive lands, regulation mechanism, servitude, land servitude, servitude relations.